Pola dan Strategi Dakwah Dalam Moderasi Beragama - Sapri Yani Hasibuan; Erwan Efendi; Deni Armanda; Yusuf Saifulloh (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Religion moderation has multiple characteristics, Indonesian society is multicultural. Culture, religion, race, language, ethnicity, tradition, and others are examples of diversity. Even though it is not a religious country, its people are closely related to religion. Life, and the constitution guarantees freedom of religion. The first precept of Pancasila,